صحابہ کرام رضی اللہ عنہم کے حدیثی مجموعے ، تعارف وتجزیہ اور استنادی حیثیت: Hadith Collections Attributed to the Companions (RA): A Critical Overview and Their Status in Islamic Scholarship (Al-Aasar, 2025)
The preservation of Hadith began during the lifetime of the Prophet Muhammad ﷺ through both memorization and writing. The Companions (Sahabah) were deeply committed to safeguarding the teachings of Islam, and they recorded both the Qur'an and Hadith. Initially, the Prophet ﷺ discouraged the writing of Hadith to avoid any confusion with the Qur'an. However, once the risk of conflation diminished, he permitted and even instructed the documentation of Hadith on various occasions. The earliest preservers and scribes of Hadith were the noble Companions themselves. Among the most prominent contributors to the compilation and transmission of Hadith were Abu Hurairah (RA), whose collections were transmitted by multiple students and documented in four notable compilations; Abdullah ibn Umar (RA), whose narrations were preserved by his students such as Nafy and Salim; and Jabir ibn Abdullah (RA), whose narrations exist in several manuscripts. Furthermore, this study highlights the contributions of other major Companions including Aisha (RA), Abdullah ibn Amr ibn al-Aas (RA), Anas ibn Malik (RA), and Ali ibn Abi Talib (RA), who played key roles in the early documentation and transmission of Hadith.